Literasi Digital: Sebuah Upaya Pelaku Pendidikan Agama Kristen dalam Membangun Integritas Remaja Gereja - Purba, Sudiarjo (Jurnal Shanan, 2022)
Christian Youth in the Sungai Bahar area of Jambi Province are active smartphone users but have not received adequate guidance in their use. This is indicated by the use of smartphones not at the time and place. This study aims to provide an educational contribution for church youth in the field of digital literacy where they have knowledge and signs in digital-related self-expression so that all their digital activities are carried out by maintaining their integrity as church youth. Trying to form a digital culture that encourages the ability to take advantage of the digital era to become a source for increasing knowledge as church’s youth. The method used in this research is a qualitative research approach with a narrative story as a research method. A study with the researcher as the person who tells and writes what has been done through digital literacy activities for Christian youth in Sungai Bahar in the form of a Day Seminar and Revival Service. The article is presented by contrasting the positive with the negative that is inherent in the life of Christian youth in the digital era with the discussion limited to only four things are: 1) producing or losting, 2) cyber bullying or cyber caring, 3) flexing or humbling), 4) cursing or blessing.